Qualidade de vida e a saúde bucal entre os idosos brasileiros : SB Brasil 2010 - Molin, Sheila Lourdes (2017)
The increase in the life expectancy at birth and the reduction of the fertility rate caused marked changes in the world age structure and with the increase in the number of elderly there is a concern for the wellbeing of this population. With advancing age, decreased motor ability, poor self-esteem, lack of stimulation to perform oral hygiene, inability to perform their own hygiene due to chronic degenerative diseases, impaired vision, hearing, and loss of the cognitive ability. These factors have contributed to poor oral hygiene and increased development of oral diseases in the elderly, which directly interfere with the general health and quality of life of this age group. Objective: To analyze the quality of life of Brazilian elderly and its association with socioeconomic and clinical factors of oral health. Methods: This cross-sectional study is an analysis of secondary data from the national oral health survey, the SB BRASIL 2010. The data were processed by the statistical package Stata version 13, using the survey command, which applies the weighting factors. To evaluate the quality of life, the Oral Impacts in Daily Performances (OIDP) was used. Results: The prevalence of the impact of the oral health on daily performances (OIDP) was 45.50% (95% CI 41.76, 49.29). It was observed that the indifferent and dissatisfied elderly with teeth and a mouth presented a prevalence of OIDP 30% and 67% higher than the satisfied elderly. Interviewees who needed dental treatment had a prevalence of OIDP 47% higher than they did not need and those who needed prosthesis for which were not needed was 42%. OIDP was 3.22 and 3.64 times more in the elderly with gingivitis and periodontitis, respectively, compared with healthy teeth. Conclusions: Although the high prevalence of oral diseases in the studied age group, their impact on quality of life is not as significant as expected. It is believed that the elderly become more tolerant of oral problems because they consider inherent to aging.